Effect of welding parameters on the fatigue properties of dissimilar AISI 2205-AISI 1020 joined by friction welding - Mercan, Serdar; Aydin, Sinan; Ozdemir, Niyazi (Elsevier Sci Ltd, 2015)
In this study, AISI 2205 duplex stainless steel, most commonly used in its class and economical AISI 1020 steel couple with low carbon content, were connected using different operation parameters through friction welding. Tension test and rotary bending fatigue test were applied to the welded connections, and the impact of the welding parameters on fatigue strength was examined. It was discovered that when the welding parameters used in connecting AISI 2205 and AISI 1020 steel couple through friction welding were selected correctly, fatigue strength of the connection would increase compared to the main material, and incompliant parameters decreased fatigue strength. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Friction welding; Fatigue; Microstructure; Stainless steel